The Mindset of (Abundance -Scarcity) among Educational Counselors - Karim, Abdul Karim Atta; Ghani, Hijran Abdul Kadhim (Journal of Ecohumanism, 2025)
The current research aims to identify the (abundance-scarcity) mentality among educational counselors. In addition to the (abundance-scarcity) mentality among educational counselors according to gender variables (males and females).To achieve the research objectives, the researchers adopted the Abbas 2019 scale, the (abundance-scarcity) mentality scale, which consists of 32 paragraphs with two alternatives. The first alternative represents the abundance mentality, and the second alternative represents the scarcity mentality.The research was conducted on a sample of (400) male and female guides from the Directorate of Education in Dhi Qar, and this sample size represents (25%) of the community. With (205) male guides at a rate of (51%) and (195) female guides at a rate of (49%) according to the gender variable, the research sample was selected using the proportional stratified random method, then the scale paragraphs were analyzed logically and statistically to calculate their discriminatory ability and validity coefficients, and the researchers verified the apparent validity and construct validity indicators of the scale, and calculated the stability of the (abundance-scarcity) mentality scale using (Kuward-Richardson stability coefficient (20) as the stability rate reached (79), and the retest method for each of the (abundance-scarcity) mentality scale, and the stability degree reached (73) for the (abundance-scarcity) mentality scale.To verify the research procedures and results, the researcher used statistical methods. She benefited from the Statistical Package for Social Sciences (SPSS) in the statistical treatments. The researchers reached several conclusions, recommendations and proposals.